1997
DOI: 10.1210/endo.138.6.5164
|View full text |Cite
|
Sign up to set email alerts
|

Preantral Ovarian Follicles in Serum-Free Culture: Suppression of Apoptosis after Activation of the Cyclic Guanosine 3′,5′-Monophosphate Pathway and Stimulation of Growth and Differentiation by Follicle-Stimulating Hormone*

Abstract: Progression of preantral follicle development is essential to further follicle maturation and ovulation, but there are few models for studying the regulation of preantral follicle survival and growth. We have evaluated preantral follicle survival in vivo and in vitro, and have developed a serum-free rat follicle culture system that can be used to characterize the regulation of preantral follicle growth and differentiation. Analysis of ovarian cell DNA fragmentation during the first wave of follicle growth in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 33 publications
10
38
0
Order By: Relevance
“…Nppc and Npr2 genes are expressed in granulosa cells of follicles and thecalinterstitial cells of rat ovaries (30,32). It has been reported that 8-bromo-cGMP can protect ovarian follicles from atresia and promote growth (33). In combination with observations that no corpora lutea and no estrus cycling were seen in null mice, the CNP͞GC-B͞cGMP system appears essential for the growth and maturation of ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Nppc and Npr2 genes are expressed in granulosa cells of follicles and thecalinterstitial cells of rat ovaries (30,32). It has been reported that 8-bromo-cGMP can protect ovarian follicles from atresia and promote growth (33). In combination with observations that no corpora lutea and no estrus cycling were seen in null mice, the CNP͞GC-B͞cGMP system appears essential for the growth and maturation of ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a two-way exchange may occur between the oocyte and granulosa cells and a direct action of FSH on oocytes produces compounds whose diffusion into the granulosa cells is necessary for their proliferation and maturation (Méduri et al, 2002). Other authors observed that FSH promotes an increase in follicular diameter and proliferation of granulosa cells (rats: McGee et al, 1997;mouse: Nayudu & Osborn, 1992;Cortvrindt et al, 1996Cortvrindt et al, , 1997Cortvrindt et al, , 1998bovine: Wandji et al, 1996;Saha et al, 2000;caprine: Silva et al, 2004;ovine: Cecconi et al, 1999;human: Roy & Treacy, 1993;Wright et al, 1999). In addition, FSH was found to stimulate antrum formation and steroidogenesis in granulosa cells (Nayudu & Osborn, 1992;Boland et al, 1993;Ralph et al, 1995Ralph et al, , 1996Wandji et al, 1996;Abir et al, 1997;Gutierrez et al, 2000;Wu et al, 2000;Mao et al, 2002;Mitchell et al, 2002;Kreeger et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor-binding Assay, cAMP, and Estradiol Production by Cultured Granulosa/Cumulus Cells-Granulosa/cumulus cells were obtained from ovaries of immature 21-day-old rats that had been implanted with diethylstilbestrol for 4 days by puncturing antral follicles with fine gauge needles; these cells were cultured in L15 medium with 0.1% BSA as described previously (60). For the receptor-binding assay, cells were resuspended in ice-cold binding buffer (20 mM Tris-HCl (pH 7.4), 2 mM MgCl 2 , and 0.1% BSA) in siliconized microcentrifuge tubes with 0.06 g of […”
Section: Methodsmentioning
confidence: 99%